2020
DOI: 10.21203/rs.2.18316/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethanol-activated CaMKII signaling induces neuronal apoptosis through Drp1-mediated excessive mitochondrial fission and JNK1-dependent NLRP3 inflammasome activation.

Abstract: Background: Neurodegeneration is a representative phenotype of patients with chronic alcoholism. Ethanol-induced calcium overload causes NLRP3 inflammasome formation and an imbalance in mitochondrial dynamics, closely associated with the pathogenesis of neurodegeneration. However, how calcium regulates this process in neuronal cells is poorly understood. Therefore, the present study investigated the detailed mechanism of calcium-regulated mitochondrial dynamics and NLRP3 inflammasome formation in neuronal cell… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In this study, we found that RCAN1 de ciency resulted in increased mitochondrial ROS production and a rapid loss of mitochondrial membrane potential. Inhibition of excessive ssion by blocking the interaction between Drp1 and mitochondrial adaptor ssion 1 (Fis1) rescued mitochondrial function, promoted survival of cardiomyocytes and reduced morbidity and mortality of septic cardiomyopathy [13,21]. By Western blotting, we found that the phosphorylation level of Drp1, the major pro-ssion marker located at the outer mitochondrial membrane, was signi cantly increased in LPS-induced RCAN1 −/− mice.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In this study, we found that RCAN1 de ciency resulted in increased mitochondrial ROS production and a rapid loss of mitochondrial membrane potential. Inhibition of excessive ssion by blocking the interaction between Drp1 and mitochondrial adaptor ssion 1 (Fis1) rescued mitochondrial function, promoted survival of cardiomyocytes and reduced morbidity and mortality of septic cardiomyopathy [13,21]. By Western blotting, we found that the phosphorylation level of Drp1, the major pro-ssion marker located at the outer mitochondrial membrane, was signi cantly increased in LPS-induced RCAN1 −/− mice.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies showed that CaMKII determines mitochondrial stress responses in heart [14]. Mitochondrial translocation of CaMKII leads to increased ROS production, enhanced mitochondrial fragmentation and mitochondrial ΔΨm deterioration, thereby promoting cell remodeling and death in septic heart [21,[28][29][30]. Unlike the effect of Drp1 dephosphorylation at Ser637 triggering its mitochondrial translocation, CaMKII induced Drp1 phosphorylation at Ser616 further activated Drp1dependent mitochondrial ssion, fragmentation and mPTP opening [16,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results thus support a novel concept that chronic accumulation of megamitochondria induced by alcohol consumption may lead to mitochondrial maladaptation resulting in liver injury. Alcohol has been shown to affect DRP1‐mediated mitochondria dynamics in cardiomyocytes, neuroblastoma cells, and engineered hepatoma cells, although the exact mechanisms remain elusive 23,36,37. TFEB is a master regulator of lysosomal biogenesis, which is impaired by alcohol consumption in hepatocytes 20.…”
Section: Discussionmentioning
confidence: 99%
“…3,37 Therefore, we further evaluated mitochondrial dynamics, mitophagy and mitochondrial functional changes in alcohol-treated myocardium. Previously, over-activated mitochondrial fission and its detrimental effects have been reported to be a key response in various organs or cell lines exposed to alcohol such as liver tissue, 57,58 brain tissue, 59 neural cells, 60 retinal pigment epithelial cells 61 and alveolar macrophages 62 exposed to ethanol challenge. In the cardiovascular system, less evidence has been reported concerning the modulatory effect of alcohol on mitochondrial dynamics although mitochondrial fragmentation has been observed in alcohol-treated myocardium.…”
Section: Food and Function Papermentioning
confidence: 99%